Activation of β-glucocerebrosidase reduces pathological α-synuclein and restores lysosomal function in Parkinson’s patient midbrain neurons - Mazzulli, Joseph R.; Zunke, Friederike; Tsunemi, Taiji; Toker, Nicholas J.; Jeon, Sohee; Burbulla, Lena F.; Patnaik, Samarjit; Sidransky, Ellen; Marugan, Juan J.; Sue, Carolyn M.; Krainc, Dimitri (Journal of Neuroscience, 2016)
Parkinson’s disease (PD) is characterized by the accumulation of α-synuclein (α-syn) within Lewy body inclusions in the nervous system. There are currently no disease-modifying therapies capable of reducing α -syn inclusions in PD. Recent data has indicated that loss-offunction mutations in the GBA1 gene that encodes lysosomal β-glucocerebrosidase (GCase) represent an important risk factor for PD, and can lead to α -syn accumulation. Here we use a small-molecule modulator of GCase to determine whether GCase activation within lysosomes can reduce α-syn levels and ameliorate downstream toxicity. Using induced pluripotent stem cell (iPSC)-derived human midbrain dopamine (DA) neurons from synucleinopathy patients with different PD-linked mutations,wefind that a non-inhibitory small molecule modulator of GCase specifically enhanced activity within lysosomal compartments. This resulted in reduction of GCase substrates and clearance of pathological α-syn, regardless of the disease causing mutations. Importantly, the reduction of α-syn was sufficient to reverse downstream cellular pathologies induced by α-syn, including perturbations in hydrolase maturation and lysosomal dysfunction. These results indicate that enhancement of a single lysosomal hydrolase, GCase, can effectively reduce α-syn and provide therapeutic benefit in human midbrain neurons. This suggests that GCase activators may prove beneficial as treatments for PD and related synucleinopathies.
CRIS-Team Scopus Importer:2020-10-21
Keywords: Glucocerebrosidase; Induced pluripotent stem cells; Lysosomes; Parkinson’s disease; Synucleinopathy; α-synuclein